Ideologie dżucze jako element silnie oddziałujący na społeczeństwo w Korei Północnej - Wróblewski, Dominik (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
The Juche ideology, despite political and economic aspects, has influenced socio-cultural aspect in North Korea. Kim Il Sung’s doctrine is an important factor that strongly unites state’s inhabitants. North Korean society, which can be called juche society, was formed on solid foundations that have historical and doctrinal conditions. Furthermore, juche’ function is to mobilize and integrate North Korean society. It is also an inspiration to community activity. It provides entity’s progress but under collective. Additionally, North Korean society shows thinking due to juche ideology. The purpose of this publication is to show juche as an important factor that influences and unites North Korean society.